Mental Health Impacts of Forced Land Evictions on Women in Cambodia. (27th September 2014) - Richardson, Jayson W.; Nash, John B.; Tan, Karen; MacDonald, Morgan
Abstract: This research examines the mental health impacts of land evictions on 40 women in Cambodia based on interviews conducted in four Cambodian provinces. The results suggest that women subjected to forced land evictions display multiple symptoms of anxiety, post‐traumatic stress disorder and depression. Women who are forcibly evicted from their homes by the Cambodian government experience sadness, compulsive worry, difficulty in sleeping, difficulty in concentrating, emotional outbursts and a preoccupation with the safety of the family. Suggestions for assistance to this population are explored. Copyright © 2014 John Wiley & Sons, Ltd.